Innovations in rural and agricultural finance: Microinsurance innovations in rural finance - Wiedmaier-Pfister, Martina; Klein, Brigette (International Food Policy Research Institute, 2010)
Poor people in developing countries are vulnerable to a broad range of shocks that affect their livelihoods, including illness, accidents, and death as well as loss of assets such as animals, crops, and machinery. The poor are still predominantly rural, and their vulnerability is even higher than that of their urban peers. Health facilities are less available and less well equipped in rural areas; water, sanitation, roads, and telecommunication are less developed; and people are less educated and not as aware of risk-mitigation mechanisms. Given the rural character of poverty in many countries, poverty reduction remains strongly connected to agricultural development, and sustainable agricultural development depends on well-organized risk mitigation. One important tool for mitigating risk is microinsurance.